Electronic consultations (e-consults) to improve access to specialty care: A systematic review and narrative synthesis. (September 2015) - Vimalananda, Varsha G; Gupte, Gouri; Seraj, Siamak M; Orlander, Jay; Berlowitz, Dan; Fincke, Benjamin G; Simon, Steven R
Background: We define electronic consultations ("e-consults") as asynchronous, consultative, provider-to-provider communications within a shared electronic health record (EHR) or web-based platform. E-consults are intended to improve access to specialty expertise for patients and providers without the need for a face-to-face visit. Our goal was to systematically review and summarize the literature describing the use and effects of e-consults. Methods: We searched PubMed, EMBASE, the Cochrane Library, and CINAHL for studies related to e-consults published between 1990 through December 2014. Three reviewers identified empirical studies and system descriptions, including articles on systems that used a shared EHR or web-based platform, connected providers in the same health system, were used for two-way provider communication, and were text-based. Results: Our final review included 27 articles. Twenty-two were research studies and five were system descriptions. Eighteen originated from one of three sites with well-developed e-consult programs. Most studies reported on workflow impact, timeliness of specialty input, and/or provider perceptions of e-consults. E-consultations are used in a variety of ways within and across medical centers. They provide timely access to specialty care and are well-received by primary care providers. Discussion: E-consults are feasible in a variety of settings, flexible in their application, and facilitate timely specialty advice. More extensive and rigorous studies are needed to inform the e-consult process and describe its effect on access to specialty visits, cost and clinical outcomes.